Proceedings of the 2nd International Arctic Ungulate Conference, Fairbanks, Alaska, 13-17 Aug 1995: Issue No. 2 - Haugerud (editor), Rolf Egil (Rangifer, 1997)
This issue of the proceedings of AUC 1995 is the2nd of four issues. Issues 1, 3 and 4 are found respectively in Rangifer 1996, 16 (2): 49-92; 1997, 17 (3): 10-138 1998, 18 (3-4): 99-154. A list of contents of the four proceedings issues is found in the latter proceedings issue.